Application of The Analytical Hierarchy Process (AHP) Method for Decision Support for Teacher Performance Assessment at Madrasah Aliyah (MA) Dail Khairaat Foundation: Penerapan Metode Analytical Hierarchy Process (AHP) untuk Pendukung Keputusan Penilaian Kinerja Guru Pada Madrasah Aliyah (MA) Yayasan Dail Khairaat - Farhan Hariri; Anita Diana (Universitas Singaperbangsa Karawang, 2021)
This research was conducted at Madrasah Aliyah (MA) Dail Khairaat Foundation, where there was an assessment method that had been carried out previously. However, there are several problems faced, namely the absence of a weighted criterion value, the large number of assessment aspects, the calculation of the final score is still manual, and it is difficult to find teacher assessment performance data. This is because the documents used are still in the form of an assessment file archive, so that it can lead to errors in teacher performance assessments. We need an assessment of teacher performance in the form of a decision support system, which produces objective and more precise results decisions, so that the results obtained are in line with expectations and can improve the quality and quality of teachers' performance. SPK teacher performance assessment uses criteria approved by the principal using the AHP (Analytical Hierarchy Process) method. The AHP method is used to generate the weighted criteria, and generate teacher alternative priorities. The research carried out resulted in a DSS with the right method for assessing teacher performance, with the weight of the criteria, and the alternative priorities of the best performing teachers. The resulting SPK is a website-based application system that can provide a recommendation for the best teacher. This DSS also makes it easier to assess, calculate and search for teacher performance appraisal data to reduce errors in teacher performance appraisals. This DSS will help the principal to make decisions to determine the best performing teachers in an objective and more precise manner. This can be used as material for evaluating teacher performance so that performance can be maintained or improved